Development and implementation of the AIDA international registry for patients with Schnitzler's syndrome - Sota, Jurgen; Vitale, Antonio; Więsik-Szewczyk, Ewa; Frassi, Micol; Lopalco, Giuseppe; Emmi, Giacomo; Govoni, Marcello; de Paulis, Amato; Marino, Achille; Gidaro, Antonio; Monti, Sara; Opris-Belinski, Daniela; et al. (Frontiers in Medicine, 2022)
Objective: The present paper describes the design, development, and implementation of the AutoInflammatory Disease Alliance (AIDA) International Registry specifically dedicated to patients with Schnitzler’s syndrome. Methods: This is a clinical physician-driven, population- and electronic-based registry implemented for the retrospective and prospective collection of real-life data from patients with Schnitzler’s syndrome; the registry is based on the Research Electronic Data Capture (REDCap) tool, which is thought to collect standardised information for clinical research, and has been realised to change over time according to future scientific acquisitions and potentially communicate with other existing or future similar registries. Results: Since its launch, 113 centres from 23 countries in 4 continents have been involved. Fifty-seven have already obtained the approval from their local Ethics Committees. The platform counts 324 users (114 Principal Investigators, 205 Site Investigators, 2 Lead Investigators, and 3data managers) at current (April 28th, 2022). The registry collects baseline and follow-up data using 3924 fields organised into 25 instruments, including patient’s demographics, history, clinical manifestations and symptoms, trigger/risk factors, laboratory, instrumental exams, therapies, socioeconomic information, and healthcare access. Conclusions: This International Registry for patients with Schnitzler’s syndrome facilitates standardised data collection, enabling international collaborative projects through data sharing and dissemination of knowledge; in turn, it will shed light into many blind spots characterizing this complex autoinflammatory disorder.